Trends in the study of Modern languages in Swedish lower secondary school (2000 – 2018) and the impact of grade point average enhancement credits. Issue 2 (3rd April 2021) - Granfeldt, Jonas; Sayehli, Susan; Ågren, Malin
ABSTRACT: This paper investigates trends in the study of Modern languages or second foreign languages (SFLs) in Swedish lower secondary school between 2000 and 2018. Over the last decades, SFLs, i.e. French, German and Spanish, have been the target of several policy measures as a response to a declining interest. However, few reports on their impact have been published. We report the proportion of pupils studying an SFL at the national level and across demographic municipality groups and analyse a possible impact of one policy measure, grade point average enhancement credits (GPAEC, meritpoäng ) for SFLs. We found an increase in the proportion of pupils studying an SFL, but mainly in urban areas. Moreover, we found important differences between SFLs. Spanish is the most widely studied SFL in all municipality groups. French is most popular in urban areas while German is more chosen in rural areas. If the increase of the number of pupils studying and SFL can be ascribed to GPAEC remains still to be seen, but if so, the GPAEC mainly had an impact on highly urban areas where the proportion of pupils studying an SFL was the highest already before introducing this policy measure.